Development of mental health first-aid guidelines for psychosis: a Delphi expert consensus study in Argentina and Chile - Agrest, Martín (2024)
Background: Psychotic symptoms may be less common than anxiety or affective symptoms, but they are still frequent and typically highly debilitating. Community members can have a role in helping to identify, offer initial help and facilitate access to mental health services of individuals experiencing psychosis. Mental health first aid guidelines for helping a person experiencing psychosis have been developed for the global north. This study aimed to adapt the English- language guidelines for Chile and Argentina. Methods: A Delphi expert consensus study was conducted with two panels of experts, one of people with lived experience of psychosis (either their own or as a carer; n = 29) and another one of health professionals (n = 29). Overall, 249 survey items from the original English guidelines and 26 items suggested by the local team formed a total of 275 that were evaluated in the first round. Participants were invited to rate how essential or important those statements were for Chile and Argentina, and encouraged to suggest new statements if necessary. These were presented in a second round. Items with 80% of endorsement by both panels were included in the guidelines for Chile and Argentina. Results: Data were obtained over two survey rounds. Consensus was achieved on 244 statements, including 26 statements locally generated for the second round. Almost 20% of the English statements were not endorsed (n = 50), showing the applicability of the original guidelines but also the importance of culturally adapting them. Attributions and tasks expected to be delivered by first aiders were shrunk in favour of a greater involvement of mental health professionals. Self-help strategies were mostly not endorsed and as were items relating to respecting the person’s autonomy. Conclusions: While panellists agreed that first aiders should be aware of human rights principles, items based on recovery principles were only partially endorsed. Further research on the dissemination of these guidelines and development of a Mental Health First Aid training course for Chile and Argentina is still required.